PREAURICULAR SINUS PRESENT AS RECURRENT EPIDERMOID CYST: ROLE OF MICROSURGERY (Vietnam Journal of Community Medicine, 2022)
Preauricular sinuses are common congenital malformations that usually occur at the anteriormargin of the ascending limb of the helix. Classically, a preauricular sinus presents as a smallopening, usually near the anterior to crus of helix and anterior-superior of tragus. The variant type ofpreauricular sinus is called postauricular sinus with location of the fistula pit positioned posterior tothe imaginary tragal extended line. In fact, preauricular sinuses can also mimic epidermoid cyst orfirst branchial cleft fistula if pit of sinus was not clear. In this study, we reported 3 rare cases ofpostauricular sinus with recurrent epidermoid cyst at anterior area of tragus and swelling atintertragal notch, the small opening “pit” of the sinuses can only be identified under a microscopyand in addition, inside- out methode seemed to be a better approach to control total ramifications withsquamous epithelium.
Keywords: Variant type of preauricular sinus, epidermoid cyst and microsurgery.